(untitled) (Journal of Asian Development Studies, 2025)
Artificial Intelligence has entered the mainstream, yet its contribution to the GDP of OECD countries remains largely unknown. This work focuses on the relationship between AI Innovation and GDP Growth, particularly AI Patents. In this work, three econometric techniques were employed: Fixed Effects (FE) models, FGLS-Parks regressions, and PCSC regressions. AI Patents positively correlate with growth for all models. Unemployment and government spending showed negative effects. The highly reanalysedconclusion records technological advancements of AI that were integrated into the economy. The unemployed and government spending positively correlate. Pegged to the artificial intelligence industry, the workforce offers great potential for the digital economy, growing in value to the (digitally) inclusive and sustainable (economy) of the (customer). The unemployed receive government support to promote and stimulate AI.